2017
DOI: 10.1088/1748-9326/aa68a5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing sustainable biophysical human–nature connectedness at regional scales

Abstract: Humans are biophysically connected to the biosphere through the flows of materials and energy appropriated from ecosystems. While this connection is fundamental for human well-being, many modern societies have-for better or worse-disconnected themselves from the natural productivity of their immediate regional environment. In this paper, we conceptualize the biophysical human-nature connectedness of land use systems at regional scales. We distinguish two mechanisms by which primordial connectedness of people t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 82 publications
2
39
0
4
Order By: Relevance
“…Landscape values connected to dimensions of a place that require experiential knowledge of it, such as harvesting possibilities and regulating ecosystem services, were connected to higher levels of responsibility, in line with Dorninger et al [7]. In a previous study [27], we found that appreciation of harvesting possibilities seems to be linked to having antecedents in the area.…”
Section: Perception Of Landscape Values and Its Connection To Place Asupporting
confidence: 88%
See 2 more Smart Citations
“…Landscape values connected to dimensions of a place that require experiential knowledge of it, such as harvesting possibilities and regulating ecosystem services, were connected to higher levels of responsibility, in line with Dorninger et al [7]. In a previous study [27], we found that appreciation of harvesting possibilities seems to be linked to having antecedents in the area.…”
Section: Perception Of Landscape Values and Its Connection To Place Asupporting
confidence: 88%
“…However, global-level policies have proven to be insufficient for avoiding unsustainable futures [6], and some authors propose that it is actually at the local and regional scales-within which social and natural factors closely interact and "humans meaningfully experience life" [7] (p. 2)-where significant change can happen. At the place-based level, individuals and communities can realise what is needed and their capabilities to take action [8,9], going beyond rhetoric and bureaucratization.…”
Section: A Global Challenge That Requires Local Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, but also as an important ontological question affecting how well we can represent feedbacks within and among human and environment systems (Ellis, 2015;Liu et al, 2015;Dorninger et al, 2017). Taken together, the frequency of communication and degree of coordination affect the degree to which feedbacks can be represented in coupled systems and, therefore, considered in our prediction of system behaviour or response to interventions (Fig.…”
Section: Approaches To Model Couplingmentioning
confidence: 99%
“…Improving our understanding of these different cross-scale dynamics in diverse land-use systems is critical. Dorninger et al (2017) conceptualize 'humannature connectedness' as a new methodological framework that can be applied in any region of the world to assess how closely connected people are to their regional ecosystems. The authors identify two key mechanisms that disconnect humans from nature on a regional scale: (1) the flow of external non-renewable inputs into the land-use system and (2) teleconnections with distant systems.…”
Section: New Framework To Understand Cross-scale Dynamics Of Land-usmentioning
confidence: 99%